Clinicopathological characteristics and long‐term outcomes of plasmablastic lymphoma in British Columbia. (12th August 2022) - Jessa, Rehan; Chien, Nicole; Villa, Diego; Freeman, Ciara L.; Slack, Graham W.; Savage, Kerry J.; Scott, David W.; Sehn, Laurie H.; Song, Kevin W.; Gerrie, Alina S.
Summary: Plasmablastic lymphoma (PBL) is an aggressive and rare subtype of non‐Hodgkin lymphoma with no standard‐of‐care therapy. We reviewed all patients diagnosed with histologically confirmed PBL in British Columbia, Canada between 1997 and 2019. Overall, 42 patients were identified, including 15 (36%) positive for HIV and nine (21%) on chronic immunosuppression. Curative‐intent treatment consisting primarily of cyclophosphamide, doxorubicin, vincristine and prednisone was administered to 31 patients, of which 74% achieved response, however 61% relapsed after a median of 7.5 months. At a median follow‐up of eight years for the whole cohort, five‐year progression‐free survival (PFS) and overall survival (OS) were 18% [95% confidence interval (CI): 6%, 30%] and 22% (95% CI: 8%, 36%) with median eight and 15 months respectively. There were no differences in relapse rate ( p = 0.962), PFS ( p = 0.228) or OS ( p = 0.340) according to immune status. For those treated with curative intent, five‐year PFS and OS were 24% (95% CI: 8%, 40%) and 31% (95% CI: 13%, 49%) with median 18 and 27 months respectively. In this population‐based cohort of PBL patients spanning 20 years, survival outcomes were poor. Ultimately, further research is needed to develop more effective treatment strategies and to improve survival for patients.